Interlingual and Intralingual Problems in Translating Short Fiction from Indonesian into English - Putri Anugraheli Ramba Orun; Abdullah Abdullah; Muhammad Fahruddin Aziz (PT ARRUS Intelektual Indonesia, 2024)
The primary objective of this study is to find out the Interlingual and Intralingual Problems faced by students in translating Short Fiction. Content analysis was used for both data collection. This study used tests and interviews to determine what errors and problems during the translation process which were then adjusted for applying relevant learning methods. The research sample consisted of 30 students majoring in English Literature. The analysis showed that most of the students needed further understanding of the use of grammar and the meaning of English words. This is due to the influence of their first language and lack of competence in the rules or structures of English. This research highlights the importance of more effective educational strategies and in-depth approaches to improve students' translation skills in English. The implications of these findings for learning methodologies are comprehensively discussed, along with suggestions for future research.